Naturally Occurring Cutaneous Anthrax: Antibiotic Treatment and Outcome - Kayabas, U.; Karahocagil, M. K.; Ozkurt, Z.; Metan, G.; Parlak, E.; Bayindir, Y.; Doganay, M. (Karger, 2012)
Objectives: Cutaneous anthrax (CA) is the most common clinical presentation in human anthrax, but the duration of antibiotic therapy in naturally occurring CA is controversial. The aim of this study was to compare the clinical outcomes of patients receiving antibiotic treatment for either 3-5 days (group 1) or 7-10 days (group 2) in uncomplicated CA. Methods: A total of 66 patients were enrolled; 29 (44%) in group 1 and 37 (56%) in group 2. Infections were classified as mild (n = 22, 33%) or severe (n = 44, 67%) CA. Results: There were no significant differences between the groups in symptom resolution time, fever clearance time, healing of lesions, development and healing of eschars, requirement for surgical intervention or the development of complications. Both edema resolution time and duration of hospital stay were longer in group 2. There were no therapeutic failures, relapses or deaths in either group. Steroid therapy was used in 32% of patients with severe CA, but a beneficial effect on resolution of edema was not demonstrated. Conclusions: These results suggest that short-course antibiotic therapy is as effective as standard-duration therapy in uncomplicated CA and that steroid therapy may not be effective. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Anthrax; Antimicrobial therapy; Bacillus anthracis; Bacterial infection; Cutaneous anthrax; Gram-positive bacteria